The influence of internet use frequency, family atmosphere, and academic performance on adolescent depression: Based on the chain mediating effect of self-adjustment and campus deviant behavior - Jiang, Mao-min; Wang, De-wen; Wu, Zheng-yu; Gao, Kai; Guo, Pei-pei; Kong, Yang (Frontiers in Psychology, 2022)
Introduction Depression has become a prominent psychological problem among young people. The purpose of this study was to investigate the potential relationship between the frequency of Internet use, family atmosphere, academic performance, self-adjustment, campus deviant behavior, and depressive symptoms among adolescents. Methods Based on the survey data of the fifth wave (2017 2018) and the sixth wave (2019 2020) of the China Family Panel Studies (CFPS), this study used LISREL8.8 software to analyze 1,577 10 15 data on adolescents. Results In this study, the mean score of self-adjustment was 42.40 (SD = 6.79), the mean score of campus deviant behavior was 12.59 (SD = 4.00), the mean score of depressive symptoms in 2018 was 11.88 (SD = 3.04), and the mean score of depressive symptoms in 2020 was 7.64 (SD = 2.20). Secondly, the frequency of Internet use had no direct effect on the depressive symptoms of adolescents, family atmosphere was negatively correlated with depressive symptoms (p < 0.005), and academic performance was positively correlated with depressive symptoms (p < 0.005). Depressive symptoms in 2020 had a direct effect (β = 0.37, p < 0.001), and also had a negative effect on depressive symptoms in 2020, with a total effect of-0.07 (p < 0.001); self-adjustment had no direct effect on depressive symptoms in adolescents in 2018, However, the total effect was −0.14 (p < 0.001), which had a significant positive effect on 2020 depressive symptoms, and the total effect was 0.18 (p < 0.001), and self-adjustment had a significant negative effect on adolescent campus deviant behavior (β = −0.38, p < 0.001); in addition, the frequency of Internet use, family atmosphere, and academic performance all had indirect effects on adolescents’ 2020 depressive symptoms, with total effects of −0.60, 0.01, and 0.02 (p < 0.001), respectively. This study also found depressive symptoms in adolescents have a certain persistence in time. Discussion Based on this study, it is necessary to pay more attention to the depression of adolescents, strengthen the training of self-adjustment, improve the anti-frustration ability and psychological resilience, and reduce the campus deviant behavior of adolescents. It is recommended to try to start from emotional self-adjustment to promote the personality health of adolescents.